Estimating the effect of rain erosion on some Sulaymaniyah districts, based on satellite (TRMM) data (Journal of the College of Basic Education, 2020)
The study area (Sulaymaniyah districts) consists of four districts (Sulaymaniyah, Chamchamal, Sharhabazar, and Darbandakhan) is located in Sulaymaniyah province, northeast of Iraq, between Qusi length (44 ° 53'30.0 "E) and 44 ° 36'54.0" (34 ° 57'24.0 "N) and 36 ° 00'19.0" N), the study aims to estimate the amount of rain erosion under the Fournier Act based on the TRMM data provided by NASA in cooperation with the Agency Japanese Aerospace Exploration (JAXA)The problem of the study is that there is no detailed study to determine whether the area suffers from a mild, moderate or severe rain erosion. The study assumed that it suffers from the weak and moderate erosion effect. It is distributed geographically in different ways from one region to another and from one month to another, (Arcgis, 10.3) in the analysis of the data, and then extraction of rain erosion for each month of the year and the extraction of the annual rate of erosion and then the rate of rainy months was extracted (12,1,2,3,4,5) The results of the analysis show that rain erosion in the study area varies from one region to another and from one month to another, depending on the fluctuation of the amount and quality of rain falling in each rainstorm, the region is dominated by the type of erosion weak, while the areas of moderate erosion in some areas and some months proportion For rainstorms, and therefore precautions must be taken to mitigate the impact of this erosion on human activities, especially on agricultural activities.